Lxs otrxs invisibles: Hacia una narrativa jurídica para la prohibición de las cirugías de “normalización genital” - Zelada, Carlos J. (2019)
Modern Medicine understands the intersex body as a pathology that must be corrected. Each year, hundreds of intersex newborns and children are subjected to genital “normalizing surgeries”: unnecessary, non-consensual and irreversible medical procedures that seek to adapt them to the status quo of corporal virtue. In this text, the authors present the main domestic and international legal discourses built around this medical practice. They conclude that, compared to national systems, International Human Rights Law has been crystalizing a legal standard prohibiting these interventions, but that it is urgent to have a contentious case before an international tribunal that so orders.